Influence of triangular wavy baffles on heat and fluid flow characteristics in a channel - Eiamsa-ard, S.; Pattanapipat, S.; Promvonge, P. (My University, 2013)
Laminar periodic flow and heat transfer in a three-dimensional channel with triangular wavy baffles (TWBs) have been numerically investigated. The baffles with three different angles of attack: 30°, 45° and 60° have been considered for Reynolds numbers ranging from 100 to 1000. For a better understanding in the heat transfer mechanisms, the pressure contour, secondary flow pattern, streamlines of impinging flow, wall streamline and iso-surface are also reported. Apparently, each wavy baffle generates two counter-rotating vortices. The 30° and 45° baffles generate vortices with comparable intensities which are considerably higher than that caused by 60° baffles. At similar conditions, the 30° and 45° baffles give comparable Nu/Nu0 values which are considerably higher than that provided by the 60° baffles, but the 30° baffles cause lower f/f 0 than the 45° and 60° baffles. For the range determined, the maximum thermal performances achieved by using baffles with the attack angles of 30°, 45° and 60° are 2.3, 2.2, and 1.88, respectively. © 2013 The Korean Society of Mechanical Engineers and Springer-Verlag Berlin Heidelberg.
Keywords: Baffle; Channel flow; Fluid flow; Heat transfer; Heat transfer enhancement